2016
DOI: 10.1093/europace/euw025
|View full text |Cite
|
Sign up to set email alerts
|

Performance of handheld electrocardiogram devices to detect atrial fibrillation in a cardiology and geriatric ward setting

Abstract: Using AliveCor or MyDiagnostick handheld recorders requires a structured screening strategy to be effective and cost-effective in a hospital setting. It must exclude patients with implanted devices and known AF, and requires targeted additional 12-lead ECGs to optimize specificity. Under these circumstances, the expenses per diagnosed new AF patient and preventable stroke are reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
143
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(177 citation statements)
references
References 17 publications
13
143
2
2
Order By: Relevance
“…An important issue was that the version of the AliveCor algorithm used by the app during the study was subsequently discovered to have undergone an intentional change by AliveCor. 16 This algorithm provided 95% sensitivity and 99% specificity in this study, which is substantially better than has been reported by Desteghe et al, 17 but was less sensitive than the earlier version of the algorithm (98% sensitivity), although with greater specificity (99% vs. 91%). 10,14 For this study, there was one case of new AF and one case of known AF, both of whom received a 'normal' algorithm interpretation, but were in AF at the time of the screening based on the research cardiologists' review.…”
Section: Discussionsupporting
confidence: 44%
“…An important issue was that the version of the AliveCor algorithm used by the app during the study was subsequently discovered to have undergone an intentional change by AliveCor. 16 This algorithm provided 95% sensitivity and 99% specificity in this study, which is substantially better than has been reported by Desteghe et al, 17 but was less sensitive than the earlier version of the algorithm (98% sensitivity), although with greater specificity (99% vs. 91%). 10,14 For this study, there was one case of new AF and one case of known AF, both of whom received a 'normal' algorithm interpretation, but were in AF at the time of the screening based on the research cardiologists' review.…”
Section: Discussionsupporting
confidence: 44%
“…The diagnostic sensitivity of the Cardiio Rhythm fingertip photoplethysmography for AF detection was 92.9%, which was higher than that of the AliveCor automated algorithm of 71.4%. The algorithm used in the AliveCor application at that time had been optimized to provide high specificity (95% CI, 99.4%–99.6%) at the expense of sensitivity (95% CI, 66.7%–71.4%), because this device was marketed to individuals rather than health professionals 30, 31. The specificity of the Cardiio Rhythm application (97.7%) was comparable to that of the AliveCor automated algorithm (99.4%).…”
Section: Discussionmentioning
confidence: 99%
“…[9] Implementation of mobile devices may provide an opportunity to address the challenges described here and aim to improve outcomes in vulnerable individuals with AF. While smartphone-based technologies are effective for screening and monitoring AF, [10,11] the data regarding their use to address adherence and HRQoL in AF remain sparse.…”
Section: Introductionmentioning
confidence: 99%